Pelatihan Supply Chain Management Untuk Peningkatan Kinerja UMKM di Bidang Manufakturing Pada CV. ADI MAKMUR METALINDO - Marwan, Marwan; Ismail, Ismail; Ridho, Farhan (LPPM Universitas Potensi Utama, 2024)
This training aims to improve the performance of Micro, Small, and Medium Enterprises (MSMEs) in the manufacturing sector through the application of Supply Chain Management (SCM) concepts and practices. MSMEs often face challenges in managing their supply chains, such as limited knowledge, operational complexity, and difficulties in adopting technology. This training is designed to equip participants with an in-depth understanding of SCM, including strategies to optimize the flow of goods, information, and finances throughout the supply chain. Participants are invited to participate in interactive sessions, including workshops, case studies, and simulations, which allow them to apply SCM theory in their own operational contexts. The results of this activity show significant improvements in operational efficiency, cost reduction, and increased competitiveness of MSMEs. The long-term impact is expected to be in the form of better business sustainability and the ability of MSMEs to compete in a wider market. This activity emphasizes the importance of SCM as a strategic tool for MSMEs to achieve sustainable growth.